A abordagem da paisagem urbana histórica e o reconhecimento de valores patrimoniais pela comunidade: o caso do Conjunto Moderno da Pampulha - Maria de Lourdes Martins Alves de Sousa (2022)
This research arises from the reflection on contemporary concepts of heritage and cultural landscape, their impacts on public policies and management procedures, and on urban sites’ monitoring and inspection practices of historical and cultural interest. It presents the issue of historic urban sites management, focusing on the recognizing of their values by their communities in order to improve the conservation strategies in contexts of permanent change. It also approaches the management of historic urban areas from the Historic Urban Landscape (HUL), considering the Pampulha Modern Ensemble as an empirical object to verify how the elements and attributes that convey the outstanding universal value of its cultural landscape - which justified its nomination as World Heritage - are perceived by the community. It relates to the revision process of the respective Management and Monitoring Plan to try verifying, through the analysis of data obtained with the application of an online questionnaire, the recognition by different social groups of the cultural landscape elements and attributes of the Pampulha Modern Ensemble that carry those values and their relation to the respective protection guidelines. The qualitative analysis of the data obtained evidences the existence of great convergence among the elements and attributes of the Pampulha landscape valued by specialists and by different segments of the community. It also verifies that several perceptions and claims pointed out by the respondents as necessary for the better enjoyment of Pampulha are present in the guidelines and actions proposed by the Management and Monitoring Plan of the Pampulha Modern Ensemble. It also argues that the community's recognition of the cultural landscape elements and attributes of the Pampulha Modern Ensemble reaffirms its importance for local life and for the sustainability of the conservation of this cultural landscape.